Socio-Psychological Specifics of Higher Education Design of Convicts in Prisons on the Basis of Information and Communication Technologies - Volov, Vyacheslav T.; Volov, Vsevolod V. (International Review of Management and Marketing, 2016)
The announced relevance of this article consists of absence investigations on higher education design for prisoners with given the specificity of the prison society. At the same time higher education is a more actual factor of personal development, behavior correction and future socialization in the society. The purpose of this article consists of the process model of higher education design on the information and communication technologies basis for convicts during their stay in prisons with the specificity of the prison environment. The leading method of this research problem is the method of simulation based on the developed mechanisms of compensate for the imbalance of personal isolation and social communication of the convicts. It allows you to treat this problem as the deliberate and organized process of the personality development of the convicted person in the intellectual, professional and emotional spheres. In the article the structure of the model of higher education design for the prisoners on the information and communication technologies includes the target, organizational, procedural, methodological, the resulting components and the feedback block, the combination of which is aimed at the development of the personality of the convicted person during his stay in the prison and further socialization after the liberation. The materials of this article are practical value for the teachers, educators and lawyers in the organization of educational process in prisons. Keywords: Penitential System (PS), Prisoner, Information-Communicational Technologies of Education, Social Isolation JEL Classifications: A23, I23, I26